Corazon y Espiritu Crematory Services feasibility study on urban crematory services - De Villa, Ommaric; Diaz, Maria Regina F.; Navarro, Charles Cole
Corazon y Espiritu Crematory Services conducted its feasibility study. The company realized the need to crematory packages as alternative to earth burials because it is less expensive and more environmentally friendly. This unrealized need of households in the local market of Caraga Region was examined. The proponents proposed low priced packages and planned to establish a cost effective and efficient crematory facility in Butuan City. The image that the company wants to project is that of good presentation, reliable, and sanitary conscious establishment. The company planned to offer a basic package competitively priced at 12,000 PhP. Market feasibility was established by studying the industry of crematory service in the local market. Demand determinants such as population growth and death rates indicated long term sustainability and stability of the project. The industry study and competitor analysis of funeral service in Caraga Region showed a great potential market for the low-priced cremation service offered by the company. Geographic and demographic segmentation was employed and the whole market of Caraga Region was targeted. The company's positioning in the market is to be the central processing center of cremation in the region. This position can be achieved by employing the marketing mix decisions made such as branding the service, offering a single basic service package, low pricing, and sufficient placement and radio promotions and based on the marketing mix, the marketing budget was established. The marketing budget is very small relative to the projections on future sales. Technical feasibility was established by identifying, evaluating and choosing among available alternatives in producing the service. Key decisions in the sequence of operations, equipment and tooling, material requirements, capacity, labor and production planning and facility design were made. The choices were based on quantitative and qualitative criteria. In particular, the group has chosen to adopt the contemporary best procedures and practices in the crematory industry and to import Crawford Elite Human Crematory System and the necessary tooling. The chosen supplier for the most important input, the liquefied petroleum gas, was Pryce Gas. This company offers the lowest price among the identified suppliers. Other inputs such as disposable caskets and biodegradable urns and cremation discs will be sourced from Republic Corrugated Cartons, Inc. and AC Steel Industries, Inc. both in Cebu City, respectively. The chosen capacity and production plans are directed to supplying a leveled supply of cremation service. The chosen plans required four (4) production personnel and three (3) administrative personnel. These requirements were the inputs in the facility system and design. Minimum requirements were satisfied and activity relationships were qualified through the process flow. Facility location was primarily based on accessibility to primary utilities such as water, electricity and communication. Other technical considerations include facility health and safety and environmental factors. The overall technical design required an initial investment of 7, 766,551. 76 pesos. The total investment cost from the 'technical study and the sales plan from the market study were used extensively to establish financial feasibility of the proposed crematory facility in Butuan City. The associated costs of the manufacturing and general administrative plans and investment and start up costs were used in estimating the financing needs of the corporation. The primary sources of financing were private investors and capitalists. The proponents chose equity financing because of low initial investment requirement and absence of interest payments from debts. The initial investments of potential investors sum to 7.90 million pesos, which is above the required total initial investment of 7.76 million pesos. Financial projections in the income statements, cash flows and balance sheets show favorable conditions of the business in the different years of projection. Retained earnings, ending cash balances and owner's equity are all positive and are steadily increasing over time. Financial measures such as return on assets (ROA) and return on equity (ROE) have attractive minimum values of 0.2133 and 0.2041, respectively. These values show the profitability of the project over the years of projection. Other relevant measures such as operating efficiency and liquidity and solvency ratios have good values and the breakeven analysis shows large marginal allowances from breakeven, which is favorable. Socio-economic evaluation was conducted to quantify the profit of the society if the project is undertaken. Net present value of 11,778,213.39 pesos is positive at the set minimum attractive rate of return (MARR) of 25% and the computed internal rate of return (IRR) of 73.62% is way above the MARR and a 8/C ratio of 4.51 indicates high benefit to cost ratio. Other benefits of the referent group also support the socio-economic feasibility of the proposed crematory facility. Thus, the proposed crematory facility is feasible. It is viable in the market, its technical design can be completely specified, it has good financial position over time and it can benefit the referent group.